Literary Theory after Populism - James A. Smith (Anglica. An International Journal of English Studies)
The article proposes three theses on the status of literary and critical theory after the populist incursions of the “long 2016.” First: that an already-ailing “theory” failed to distinguish itself from professional class anti-populism during the political upheavals of Trump, Brexit, Corbyn, Bernie Sanders, and others. Second: that there is within literary theory’s history a concealed tradition of “literary populism”; the normative belief that good or desirable writing has some surreptitious connection to the idioms of ordinary people. And third: that there are lessons to learn from the broadly forgotten episode of Terry Eagleton’s critique of Raymond Williams in the late 1970s – where the charge was that Williams himself was a populist.